Analysis of Empirical Research on the Factors Influencing the Change of Income Inequality - Diliuvienė, Laura; Tamašauskienė, Zita (Socialiniai tyrimai, 2019)
Until the last major recession, there was an approach in macroeconomics that income distribution was not significant for macroeconomic processes. However, the recent major recession has prompted policymakers and economists to take into account the phenomenon of income inequality, its economic and social causes and consequences related to poverty, social inclusion, social trust, support of democratic institutions, economic growth, financial and other issues.In recent years, income inequality has been rising in many countries, and the International Monetary Fund, the OECD and other organizations underline the importance of addressing this problem. It is important to choose the right measures to make the right decisions in order to address the issues of growing income inequality. Their choice is influenced by the identification of factors influencing the change of income inequality and the impact assessment.The scale and change of income inequality can be influenced by the factors related to the market economy (globalization, technological progress) and the institutional factors (setting the rules of the game on the market, creating a certain environment). According to the factors analysed in the research, three groups of authors can be distinguished. Some authors (Asteriou, Dimelis, Moudatsou, 2014, Cabral, García-Díaz, Mollick, 2016, Lim, McNelis, 2016, Sheng, 2015, Haan, Sturm, 2017, Wade, 2004, Alvarez, 2015, Elmawazini, Sharif, Manga, Drucker, 2013, Jaumotte, Lall, Papageorgiou, 2013, Çelik, Basdas, 2010, Hermes, 2014, Richmond, Triplett, 2017, Franco, Gerussi, 2013, Stockhammer, Guschanski, Köhler, 2016, Soons, 2016, Jaumotte, Lall, Papageorgiou, 2008) investigate and assess the impact of market factors (globalization, financialization, technological progress) on income inequality, while other authors or the group of authors (IMF, 2014, Arestis, Gonzalez-Martinez, 2016, Checchi, Josifidis, Supic, Beker Pucar, 2017, Feld, Schnellenbach, 2014, Obadić, Šimurina, Sonora, 2014, Calderón, Chong, 2009, Checchi, García-Peñalosa, 2008, Saez, 2017, Jaumotte, Buitron, 2015, Bastagli, Coady, Gupta, 2012, Kenworthy, Pontusson, 2005) distinguish the impact of institutional factors (labour market institutions, welfare state) on income inequality. According to J. E. Stiglitz (2016), the market does not operate in a vacuum – it operates within an institutional setting. Therefore, the third group of authors can be identified that assess the impact of both market and institutional factors on inequality (Stiglitz, 2016, Atkinson, 2003, Josifidis, Supic, 2017, Josifidis, Mitrović, Supić, Glavaški, 2016, Huber, Stephens, 2014, Darcillon, 2015, Lin, Fu, 2016, Ghossoub, Reed, 2017, Kristal, Cohen, 2017, Alderson, Nielsen, 2002, Kus, 2012, Tridico, 2015, Dabla-Norris, Kochhar, Ricka, Suphaphiphat, Tsounta, 2015, Jain-Chandra, Kinda, Kochhar, Piao, Schauer, 2016). The results of empirical studies assessing the impact of different factors on income inequality are contradictory. There is a disagreement on the distinction between different factors influencing the change of inequality as well as the direction and strength of their impact. Therefore, it is relevant to determine what factors determine income inequality and what is their impact on income inequality.The aim of the research is on the basis of empirical research to analyse the impact of factors influencing the change of income inequality, to identify which factors have the greatest impact. Research methods are as follows: analysis, grouping and generalization of scientific articles.On the basis of the analysis of the studies, which evaluated the factors determining income inequality, five groups of factors determining income inequality have been identified: 1) globalization; 2) technological progress; 3) financialization; 4) labour market institutions; 5) welfare state. It is possible to state that some studies assess the impact of only one set of factors on the change of income inequality: globalization, financialization, labour market institutions or technological progress, while other studies assess more than two groups of factors. This reflects the authors’ differing views on the factors and how they influence the change of income inequality.On the basis of the empirical results analysed in this research, it can be concluded that globalization tends to increase income inequality. However, the results of some studies show that globalization increases income inequality in both developed and developing countries, while the results of other studies show that globalization reduces income inequality in developing countries. The research assessing the impact of factors determining income inequality in EU countries (Asteriou, Dimelis, Moudatsou, 2014) found that in some countries (Austria, Belgium, Germany, France, Luxembourg, the Netherlands, the United Kingdom, Greece, Italy, Ireland, Portugal, Spain) the globalization led to the decrease in income inequality and in other countries (Finland, Sweden, Denmark and the new EU countries) it led to the increase. It has been found that: 1) the impact of trade globalization on changes of income inequality is ambiguous: in some studies it reduces income inequality, in others it increases income inequality or the impact is insignificant; 2) the impact of financial globalization on changes of income inequality is usually positive.Summarizing the impact of technological progress on income inequality, it has been found that technological progress increases income inequality, but the use of information and communication technologies (Internet and mobile communication) reduces income inequality. The impact of the group of financialization factors on income inequality is also ambiguous: 1) financial deepening increases income inequality by investigating the impact in many countries of the world, but it decreases it in developed countries; 2) if the impact of some financial development indicators on inequality is insignificant, then the impact of ratio between bank credits and GDP increases income inequality; 3) financial liberalization increases income inequality; 4) banking crises increase income inequality; 5) the intensity of microfinance reduces income inequality. One of the indicators of labour market institutions (trade union membership) is mentioned in the studies as both reducing and increasing (through channels of wage differences and unemployment rate) income inequality. The results of empirical research show that income inequality is reduced by labour protection laws, bargaining power in wage setting, and it is increased by labour market flexibility, capital per worker (through part of work and unemployment channels) and the ratio of minimum and average wage (through the gap of pay and unemployment rate channels). The factors of welfare state have a positive impact and reduce income inequality.The results of the research do not provide an unambiguous answer, but most evidence shows that labour market institutions and welfare state factors reduce income inequality, while factors of technological progress and financialization increase income inequality. In summary, technological advances, labour market institutions and globalization have the greatest impact on changes of income inequality.
Keywords: income inequality; globalization; technological change; financialization; labour market institutions; welfare state